The Relationship Of Anemia In Pregnancy With The Event Of LBW Babies (Low Birth Weight) at Supiori Hospital - Sri Wahyuni; Arsity Rian Avinda Putri; Sarah Imbir (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Background: Anaemia is a common medical problem in pregnancy. The extent up to which, maternal anaemia effects maternal and neonatal health is still uncertain. Maternal anaemia is commonly considered a risk factor for low birth weight (LBW) babies. The purpose of this study was to determine the relationship between anemia in pregnancy and the incidence of LBW infants in Supiori Hospital. This research method used an analytical survey with a cross sectional approach by looking at the medical record data at the Supiori Hospital in Januari-May 2021 who giving birth as many as 80 responden. Sampling technique with total sampling. Bivariate analysis used chi-square. Results: Bivariate analysis showed statistical test results using chi-square obtained a significant value, namely 0.000 <0.05. Conclusion: There was a relationship between pregnancy and anemia with the incidence of LBW infants in Supiori Hospital.